HA/CD44 Regulates the T Helper 1 Cells Differentiation by Activating Annexin A1/Akt/mTOR Signaling to Drive the Pathogenesis of EAP - Chen, Jing; Meng, Jialin; Li, Xiaoling; Li, Xiao; Liu, Yi; Jin, Chen; Zhang, Li; Hao, Zongyao; Chen, Xianguo; Zhang, Meng; Liang, Chaozhao (Frontiers in Immunology, 2022)
CD44 partcipates in multiple inflammatory reactions. Here, we aimed to investigate the role of CD44 and the ligand, Hyaluronan (HA), on CP/CPPS pathogenesis. We found that CD44 was universally expressed on CD4+ lymphocytes in peripheral blood of CP/CPPS patients. After silencing CD44 expression or delivering 4-MU, the pain severity and prostatic inflammation were significantly relieved. In vitro assay found that HA/CD44 was able to regulate Th1 cell differentiation, and the difficiency of which, diminished EAP susceptibility. Bioinformatic analysis suggested that after HA or 4-MU treatment, mTOR signaling was significantly altered, and these results were confirmed by subsequent western blotting assay. Besides, mass spectrometry and Co- Immunoprecipitation assays found that CD44 was able to interact with Annexin A1 (ANX A1), and this kind of interaction stabilized ANX A1 protein, maintained the activation of AKT/mTOR pathway. Meanwhile, HA treatment enhanced prostatic inflammation, Th1 cell differentiation, and AKT/mTOR pathway activation were reversed after silencing the expression of ANX A1 using shANX A1-lentivirus. The present study systematically investigates the functional role of HA/CD44 in CP/CPPS, and identifies novel mechanisms for HA/CD44 promotes Th1 cell differentiation. Targeting the HA/CD44/ANX A1/Akt/mTOR signaling represents novel potential therapeutic strategies for patients with CP/CPPS.